Large extinct canids from the Pleistocene of Uruguay: systematic, biogeographic and paleoecological remarks - Prevosti, Francisco Juan (2009)
The fossil record of Canidae in South America begins in the Late Pliocene. During the Pleistocene large hypercarnivorecanids (Theriodictis, Protocyon, Canis dirus) and also large species of Neotropical foxes (Dusicyon avus) evolved. Mostfossil canids were found in Chile, Ecuador, Bolivia, Brazil, Venezuela and Argentina and are scarce or absent in othercountries. From Uruguay only fossils referred to Dusicyon gymnocercus, ‘Pseudalopex’ and ‘Canis’ are currently known.We describe new records that belong to large canids from the Sopas Fm. (Late Pleistocene) of Uruguay and discuss theirbiogeographic and paleoecologic relevance. These specimens are referred to Protocyon troglodytes and D. avus by means ofdescriptive and multivariate analysis and constitute the first records of these taxa for Uruguay, expanding and completingtheir distribution in the Late Pleistocene of South America. Both species could have been occupied ‘niches’ not representedby the carnivores previously registered in the Sopas Fm. (Puma concolor, Panthera onca, Lontra longicaudis, etc.)suggesting more complex biotic interactions in the mammalian assemblages than previously assumed. The largehypercarnivorous canid P. troglodytes could hunt medium-large sized mammals, pursuing their prey in packs over longdistances, while the medium canid D. avus could prey on small and middle mammals.